Rapamycin rejuvenates oral health in aging mice - An, Jonathan Y; Kerns, Kristopher A; Ouellette, Andrew; Robinson, Laura; Morris, H Douglas; Kaczorowski, Catherine; Park, So-Il; Mekvanich, Title; Kang, Alex; McLean, Jeffrey S; Cox, Timothy C; Kaeberlein, Matt (eLife, 2020)
Periodontal disease is an age-associated disorder clinically defined by periodontal bone loss, inflammation of the specialized tissues that surround and support the tooth, and microbiome dysbiosis. Currently, there is no therapy for reversing periodontal disease, and treatment is generally restricted to preventive measures or tooth extraction. The FDA-approved drug rapamycin slows aging and extends lifespan in multiple organisms, including mice. Here, we demonstrate that short-term treatment with rapamycin rejuvenates the aged oral cavity of elderly mice, including regeneration of periodontal bone, attenuation of gingival and periodontal bone inflammation, and revertive shift of the oral microbiome toward a more youthful composition. This provides a geroscience strategy to potentially rejuvenate oral health and reverse periodontal disease in the elderly. Age is the single greatest risk factor for many human diseases, including cancer, heart disease, and dementia. This is because, as the body ages, it becomes less able to repair itself. One way to prevent age-related disease and extend lifespan, at least in laboratory animals, is to use a drug called rapamycin. Mice treated with rapamycin live longer, have stronger hearts, and respond better to vaccination. But, despite these promising observations, the use of rapamycin as an anti-aging treatment is still under investigation. One open question is what age-related diseases rapamycin can help to prevent or treat. In the United States, more than 60% of adults over the age of 65 have gum disease. These people are also more likely to have other age-related diseases, like heart disease or Alzheimer's. This association between gum problems and other age-related diseases prompted An et al. to ask whether it might be possible to treat gum disease by targeting aging. To find out whether rapamycin could improve gum health, An et al. performed three-dimensional CT scans on mice as they aged to measure the bone around the teeth. Some of mice were treated with rapamycin, while the rest received a placebo. The mice that received the placebo started to show signs of gum disease as they aged, including inflammation and loss of bone around the teeth. The types of bacteria in their mouths also changed as they aged. Treating mice with rapamycin not only delayed the onset of these symptoms, but actually reversed them. After eight-weeks of the drug, the older mice had lost less bone and showed fewer signs of inflammation. There was also a shift in their mouth bacteria, restoring the balance of species back to those found in younger mice. Rapamycin is already approved for use in people, so a clinical trial could reveal whether it has the same effects on gum health in humans as it does in mice. But there are still unanswered questions about how rapamycin affects the mouth as it ages. These include how the drug works at a molecular level, and how long the changes to gum health persist after treatment stops.